Two-Way Bending of Base Plates under Uniaxial Moment Loading–Alternative Approach - Haninger, Edward R.; Tong, Bruce M. (Engineering Journal, 2014)
This Technical Note presents an alternate model for two-way bending design of column base plates under uniaxial moment loading and is based on the design premises of AISC Design Guide 1, Base Plate and Anchor Rod Design (Fisher and Kloiber, 2006). Two-way bending, in this paper, refers to bending of a column base plate in the direction perpendicular to the primary direction of bending and is also called side bending. When two-way bending governs, which is commonly the case, this procedure results in more efficient base plates that more closely reflect available strengths. A sample calculation is also provided.